PEMANFAATAN ALAT TANGKAP IKAN TRADISIONAL OLEH NELAYAN PULAU BAWEAN KABUPATEN GRESIK - Nafsul Mutmainnah; Iis Nur Asyiah; Ika Lia Novenda (JURNAL PERIKANAN TROPIS, 2021)
Bawean Island is located in the middle of the Java Sea, about 150 km north of Gresik. The name Bawean was taken from the Sanskrit which means there is sunlight. The Bawean people are acculturation from several ethnic groups of Java, Madura, Kalimantan, Sulawesi and Sumatera including their culture and language. The majority of Bawean residents work as fishermen. Bawean Island fishermen utilize marine resources to meet the needs of their family by using knowledge that has been obtained from previous generations. The purpose of this study was to determine the use of traditional fishing gear and fishing strategies used by fishing communities in Bawean Island. The research method used was direct observation, and sampling using Purposive Sampling and Snowball Sampling. The results showed that the fishing gears used by Bawean Island fishermen were kareket (waring), pajeng (payang), jhering cursor (ring net), rompon (bubu), jhering pemhir (drift gill net), payimbek rentengan (drag fishing), gerany Panyimbek (drag fishing line), panceng (fishing line). These fishing gears are very environmentally friendly because the usage does not damage the seabed ecosystem. Each fishing gear has its own characteristics, so that different fishing gear will result in different fishing catch